Reimagining Malcolm X - John Andrew Morrow (International Institute of Islamic Thought, 2016)
At 84-pages, Reimagining Malcolm X: Street Thinker Versus Homo Academicus by Seyed Javad Miri is more of a booklet than a book. In fact, like most of the 40 books on sociology and religion published by this scholar, many of which are self-published or released by subsidy publishers, it falls into that awkward category between an essay that is too long and a book that is too short. Considering the fact that most university and independent academic presses place profit and marketability before contribution to scholarship in the field, the fact that ambitious and prolific academics seek to be proactive and find alternate modes of sharing their scholarship should be commended. Consequently, scholars working in the field of sociology and religion should be grateful to both Miri and the University Press of America for making this work on Malcolm X available to readers and researchers. Reimagining Malcolm X examines the significance of el-Hajj Malik el- Shabazz as a social theorist by analyzing his views on race, academia, philosophy, and politics. The work is divided into four chapters: “Novel Strategies of Interpretation,” “Undisciplinary Fields of Knowledge,” “Violence, Religion, and Extremism,” and “The Epic of America.” In chapter 1, Miri points out that “Malcolm X has not been appropriated within the body of academic social sciences as he should have been” (p. 9). This is both obvious and intentional. It is heartening, however, to see that interest in Malcolm’s thoughts has extended to certain segments of Iranian academia. As the author reveals, however, some Iranian scholars are reticent to see the value of Malcolmian theories and concepts (p. xi). Despite all of its revolutionary rhetoric, the Islamic Republic of Iran has shown little interest in el-Hajj Malik el-Shabazz. On the contrary, it has preferred to invite his nemesis Louis Farrakhan, a man who admits that he created the conditions that lead to Malcolm’s assassination, to preach at the seminary in Qum. Considering that the Iranian regime considers itself the bastion of Shi‘ite orthodoxy and cracks down on both political critics and practitioners of taṣawwuf (‘irfān or Sufism), it is ironic that its leaders have promoted a man who believes that W. D. Fard was the incarnation of Allah and that Elijah Muhammad, as opposed to Muhammad ibn ‘Abd Allah, was Allah’s final ...